Motives and Construction of Independence, Competence, and Innovation Millenial Generation in Electronic - Subagyo Adam, Moch. Ali Mashuri, (Opción, 2019)
The purpose of this study is to understand the meaning of independence, competence, millenial generation innovation in the improvement of electronic-based services at the Department of Investment and Integrated Service One Door Sidoarjo regency. The research method used is qualitative. As a result, the potential of millennial generation can be constructed according to different characteristics in providing public services in the field of licensing. So in providing public service generation millennial have independence, competence, and innovation. In conclusion, the labor force has a motive in working are achievement, reward, responsibility, honesty, and cooperation.